Recent progress and development of vibration-assisted metal forming process - Zhichao Xu; Haolun Yang; Wenju Yang; Heshuai Yu; Xuefeng Guo; Hucheng Pan; Gaowu Qin (Journal of Materials Research and Technology)
Ultrasonic vibration-assisted plastic processing technology effectively reduces the forming force during metal processing and enhances the overall performance and processing quality of materials by exploiting the surface and volume effects of ultrasonic vibration. It is an environmentally friendly and energy-efficient technology. This article reviews the use of ultrasonic vibration in alloy deformation, examining the macroscopic performance, process characteristics, and recent research developments of typical plastic forming processes within vibration fields. Building on this foundation, the mechanisms of vibration-assisted plastic forming are summarized, with a focus on the stress superposition effect, acoustic softening effect, and acoustic residual effect. Additionally, based on the vibration-induced friction reduction and friction models in vibration fields, this paper reviews research on the interface friction behavior in vibration-assisted plastic forming. The main issues in the theoretical and applied research of ultrasonic vibration plastic forming of metals are identified. Finally, the development prospects of vibration-assisted metal forming technology are promising, and the main challenges, as well as future research directions in ultrasonic vibration-assisted plastic forming of metals, are explored.